EKSPEKTASI WISATAWAN MANCANEGARA TERHADAP KENYAMANAN AREAL PARKIR DIKAWASAN DAYA TARIK WISATA PANTAI KUTA KABUPATEN BADUNG - Putra Yasa, Ngakan Ketut; Sukana, I Made (JURNAL DESTINASI PARIWISATA; Vol 2 No 2 (2014): VOL 2, NO 2 (2014): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2014.v02.i02.p10, 2014)
Abstract Badung is one of regency in Bali ha ve much of tourism potential , tourist attraction and tourism resources. Currently Badung Regency have been developing Kuta Beach tourism . This research will discuss about Expectation Against Foreign Tourists In Area Parking Leisure Travel Attractions of Kuta Beach. This prompted a large number of tourists both domestic and foreign, thus the need for the development of the means of better facilities associated with supporting facilities and infrastructure for the comfort of tourists visiting Kuta beach. One of them in the provision of tourist services in the form of comfort in the parking area of ??Kuta beach tourist attraction for foreign tourists. Determination engineering samples used in this study is the method of purposive sampling Accidental sampling is coincidentally the foreign tourists who visit the area to Kuta beach tourist attraction. While the technique of determining purposive informant here is done by the special purpose. Purposeful (purposive) is used as a strategy when one wants to learn something and come to understand something about the cases of certain options need not generalize to all such cases (Patton, 1980:100). The collected data was then analyzed using qualitative descriptive. As early as the 1960s until today, Kuta is known as the busiest tourist spots in Bali. Understanding the expectations of his own wish fulfillment (hope) the traveler is a long process, to take a long time and are not cheap to achieve something as expected. This expectation for improvement exert towards something better and can be felt. Foreign tourists will want a change in their perceived shortcomings. This is due to the parking area of ??land that is not in accordance with the number of tourists who visit each day. Moreover, the land often take the road shoulder parking lot that resulted in severe congestion, especially for users of the road to access the beach of Kuta. Leisure tourists became distracted.
Keywords: Ekspectation, Tourist, Comfortable, Parking Area.